2005
DOI: 10.1002/eat.20123
|View full text |Cite
|
Sign up to set email alerts
|

The process of recovery in eating disorder sufferers' own words: An Internet-based study

Abstract: This exploratory Internet-based study attempts to understand what eating disorder sufferers suggest when they mention the word recovery. All messages (N = 685) posted in a Finnish-language eating disorders discussion group during a 3-month period were analyzed for the contexts of the word recovery using text analysis software and qualitative methods. The discussion group participants' views of recovery changed according to their current stage of change. Mentioning recovery was least likely during precontemplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(66 citation statements)
references
References 15 publications
4
62
0
Order By: Relevance
“…It was not a very effective way because it was just ignoring what was going on… but I guess at the time, that was the only thing I had.' [38] (c) Denial of Disease [3,[5][6][7]11] . This eating behavior is considered normal by some patients, since they do not consider themselves mentally ill.…”
Section: Symptom Identification Disease Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not a very effective way because it was just ignoring what was going on… but I guess at the time, that was the only thing I had.' [38] (c) Denial of Disease [3,[5][6][7]11] . This eating behavior is considered normal by some patients, since they do not consider themselves mentally ill.…”
Section: Symptom Identification Disease Representationmentioning
confidence: 99%
“…The results of this research reveal a complex structure characterized by the presence of many variables, outstanding among which are various ways of understanding the disease, peculiarities of personal history, emotional difficulties, and the structure of family dynamics [3][4][5] . Other studies have identified experiences related to rejection, low self-esteem, insecurity, and autoevaluation centered on the body [6][7][8] . As would be expected, most research has involved small samples, generally from 1 to 12 patients [3,[9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…21 Two studies used male and female participants. 12,25 Eating disorders are much less frequent in men than in women. For that reason, men have been relatively neglected and ignored by specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Empathic understanding and support emerged as the most common factors. 25 a) Factors that contributed to production of change:…”
Section: Recoverymentioning
confidence: 99%
“…Pettersen & Rosenvinge, 2002;Rahkonen & Tozzi, 2005;Tozzi et al, 2003) provide compelling evidence that treatment do contribute to recovery or a recovery process.…”
Section: Treatment Factorsmentioning
confidence: 99%